1992
DOI: 10.1128/jb.174.18.5814-5819.1992
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of an Erwinia herbicola gene necessary for gluconic acid production and enhanced mineral phosphate solubilization in Escherichia coli HB101: nucleotide sequence and probable involvement in biosynthesis of the coenzyme pyrroloquinoline quinone

Abstract: Escherichia coli is capable of synthesizing the apo-glucose dehydrogenase enzyme (GDH) but not the cofactor pyrroloquinoline quinone (PQQ), which is essential for formation of the holoenzyme. Therefore, in the absence of exogenous PQQ, E. coli does not produce gluconic acid. Evidence is presented to show that the expression of an Erwinia herbicola gene in E. coli HB101(pMCG898) resulted in the production of gluconic acid, which, in turn, implied PQQ biosynthesis. Transposon mutagenesis showed that the essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 19 publications
0
90
0
1
Order By: Relevance
“…It has been speculated that the cysteine residues of the highly conserved "cysteine box" GX-CXXXCXXCXQ motif of these proteins are involved in [Fe-S] cluster binding. This is supported by the fact that an identical motif is found in other [Fe-S] cluster proteins such as LIPA (Swiss-Prot accession number P25845) (19), ARR-AE (P39329) (32), LAM (33), the nitrogen fixation B gene product (P11067) (34), pyrrolo-quinoline-quinone synthase (Q01060) (35), PFL-AE (P09374) (17), NARA protein (P39757) (36), FNR (P03019) (37), benzylsuccinate synthase-activating enzyme (CAA05050) (38), spore photoproduct lyase (P37956) (39), molybdenum cofactor synthase (O27593) (40), and the thiamine synthase H gene product (P30140) (39). Mutational studies on PFL-AE have shown that the three cysteine residues of the cysteine box are vital for its activity (41).…”
Section: Indicating That the [Fe-s] Cluster Is Lost Under The Ms Condmentioning
confidence: 76%
“…It has been speculated that the cysteine residues of the highly conserved "cysteine box" GX-CXXXCXXCXQ motif of these proteins are involved in [Fe-S] cluster binding. This is supported by the fact that an identical motif is found in other [Fe-S] cluster proteins such as LIPA (Swiss-Prot accession number P25845) (19), ARR-AE (P39329) (32), LAM (33), the nitrogen fixation B gene product (P11067) (34), pyrrolo-quinoline-quinone synthase (Q01060) (35), PFL-AE (P09374) (17), NARA protein (P39757) (36), FNR (P03019) (37), benzylsuccinate synthase-activating enzyme (CAA05050) (38), spore photoproduct lyase (P37956) (39), molybdenum cofactor synthase (O27593) (40), and the thiamine synthase H gene product (P30140) (39). Mutational studies on PFL-AE have shown that the three cysteine residues of the cysteine box are vital for its activity (41).…”
Section: Indicating That the [Fe-s] Cluster Is Lost Under The Ms Condmentioning
confidence: 76%
“…Because germination stage is the most susceptible period in rice life cycle 39 . Rice growth promotion can be achieved by beneficial bacteria but the exact mechanism by which PGPB induce their effects is not clearly understood, however, several hypotheses such as producing phytohormones, activation of phosphate solubilization and promotion of the mineral nutrient uptake are usually considered to be involved 8,14,26,29 . Production of phytohormones is one of the important mechanism and indole-3 acetic acid (IAA), which is a member of native auxin, is a common metabolism produced by several beneficial bacteria 31 .…”
Section: Introductionmentioning
confidence: 99%
“…From similar studies, six (possibly seven) pqq genes have been postulated in M. organophilum DSM760 (4). Finally, a DNA fragment cloned from Erwinia herbicola contained a gene encoding a protein similar to K. pneumoniae PqqE and A. calcoaceticus PqqIII (22). Except for the K. pneumoniae PqqF protein, none of the Pqq proteins shows similarity to other proteins in the database.…”
mentioning
confidence: 98%